EFEKTIVITAS PENERAPAN TEKNIK ASEPTIK OLEH PERAWAT DALAM PEMASANGAN INFUS TERHADAP KEJADIAN FLEBITIS DI RUANG CEMARA 1 RS BHAYANGKARA TK I RS SUKANTO - Ni Luh Gede Vidya Gayatri, (2022)
Phlebitis is an inflammation of the punctured vein with symptoms of pain, redness, or swelling at the stabbing area. According to a survey conducted in Indonesia, the number of phlebitis cases varies, the incidence rate is 50.11% for government hospitals, while private hospitals are 32.70%. This writing aims to measure the effectiveness of the application of aseptic by nurses in infusion to the incidence of phlebitis. The method of data collection is using a questionnaire sheet and observing the action. Based on the results of the questionnaire obtained in the Cemara 1 Hospital Bhayangkara TK. 1 R. Said Sukanto, 87.5% have good knowledge, 25% have good characteristics in the application of aseptic techniques. The results of the observation after the action, changed from 37.5% to 100% applying aseptic techniques in infusion to the incidence of phlebitis. The author hopes that every time the nurse performs an infusion, the nurse pays attention to aseptic measures that will reduce the incidence of phlebitis. Keywords: Aseptic technique, Infusion Installation, Phlebitis